Economic influence of corrosion on mild steel in an industrial setup: An overview - Samuel Adebanji Ajayi; Olufemi Ajide; Abideen T. Oyewo; Ejiroghene Onokpite; Agberegha Larry Orobome; Christian O. Osueke (Researcher and Lecturer Society, 2026)
Most manufacturing industries throughout the world are facing many corrosion problems. Contaminants such as CO2 and H2S which deteriorate pipe lines and machine components made from mild steel are the major challenge of these industries. Corrosion is a pervasive and financially detrimental process that significantly impacts industrial operations, with mild steel being particularly susceptible due to its widespread use and inherent reactivity. This paper examines the multifaceted economic influence of mild steel corrosion within an industrial setting, distinguishing between direct and indirect costs. The direct economic burden includes expenses related to frequent maintenance, repair, and premature replacement of corroded assets, as well as capital costs associated with overdesign and the implementation of corrosion control measures. Indirect costs, often more substantial and difficult to quantify, encompass losses from production downtime, decreased operational efficiency, product contamination, and environmental cleanup. By synthesizing data from various industrial sectors, this paper highlights that the total cost of corrosion represents a considerable percentage of a nation's Gross Domestic Product (GDP). Proactive corrosion management, including the strategic use of coatings, cathodic protection, and material selection, is identified as a critical factor in mitigating these financial losses and enhancing the longevity, safety, and profitability of industrial infrastructure.